The Pleistocene Witch Ground Ice Stream in the central North Sea - Benedict T. I. Reinardy; Jens Karstens; Christoph Böttner; Anna Lichtschlag; Christian Berndt; Nichola A. Strandberg; Ben J. Callow (Journal of Quaternary Science, 2025)
The North Sea Basin has been covered by ice sheets originating from both the British Isles and Scandinavia at multiple times during the Pleistocene. The Witch Ground Basin (WGB) in the central northern North Sea is a critical location in terms of interpreting Late Pleistocene glacial to glacimarine history of the North Sea since it was the location of the Witch Ground Ice Stream that was active on multiple occasions during the Mid to Late Pleistocene. We map five mega‐scale glacial lineation flowsets corresponding to the changing ice flow direction of the Witch Ground Ice Stream and investigate the sedimentological fingerprint and corresponding subglacial depositional processes of this palaeo‐ice stream. We show that sorted sand layers within a subglacial traction till represent periodic hydraulic jacking and ice–bed decoupling at the base of the Witch Ground Ice Stream. In contrast to previous studies that have described glacitectonites deposited below the most recent grounded ice in the WGB, we present analysis of sediment cores that recovered primarily massive diamictons without any obvious deformation structures. The most recent ice cover in the WGB (~18–16 ka) was thought to have been sourced from a localized ice cap over Orkney and Shetland. The presence of chalk clasts sourced from NW of the WGB described in this study from the stratigraphically youngest till confirms this interpretation. The transition from subglacial to glacimarine deposition, while acoustically well defined (from opaque to laminated acoustic units), appears surprisingly uniform in the recovered sediment cores, but can be differentiated based on a change in colour including mottling and banding, presence of whole intact shells, and the increased number of silt and sand lenses. 14 C dating of glacimarine muds indicate high sedimentation rates of between 80 and 260 cm ka −1 . The transition from glacimarine to marine deposition is represented by a comparative decrease in sedimentation rate and deposition of Holocene age sandy mud. This study demonstrates a highly dynamic Witch Ground Ice Stream in the northern North Sea during the Late Pleistocene with evolving subglacial hydrology and depositional processes at the ice stream bed that left a distinct geomorphological and sedimentological fingerprint within the WGB.

Influence of Local Aperture Heterogeneity on Invading Fluid Connectivity During Rough Fracture Drainage - Tomos Phillips; Tom Bultreys; Jeroen Van Stappen; Kamaljit Singh; Sahyuo Achuo Dze; Stefanie Van Offenwert; Ben Callow; Mostafa Borji; Erik Clemens Boersheim; Vladimir Novak; Christian M. Schlepütz; Veerle Cnudde; et al. (Transport in Porous Media, 2024)
Determining the (in)efficiency of wetting phase displacement by an invading non-wetting phase (drainage) in a single fracture is key to modelling upscaled properties such as relative permeability and capillary pressure. These constitutive relationships are fundamental to quantifying the contribution, or lack thereof, of conductive fracture systems to long-term leakage rates. Single-fracture-scale modelling and experimental studies have investigated this process, however, a lack of visualization of drainage in a truly representative sample at sufficient spatial and temporal resolution limits their predictive insights. Here, we used fast synchrotron X-ray tomography to image drainage in a natural geological fracture by capturing consecutive 2.75 μm voxel images with a 1 s scan time. Drainage was conducted under capillary-dominated conditions, where percolation-type patterns are expected. We observe this continuously connected invasion (capillary fingering) only to be valid in local regions with relative roughness, λ b ≤ 0.56. Fractal dimension analysis of these invasion patterns strongly aligns with capillary fingering patterns previously reported in low λ b fractures and porous media. Connected invasion is prevented from being the dominant invasion mechanism globally due to high aperture heterogeneity, where we observe disconnected invasion (snap-off, fragmented clusters) to be pervasive in local regions where λ b ≥ 0.67. Our results indicate that relative roughness has significant control on flow as it influences fluid conductivity and thus provides an important metric to predict invasion dynamics during slow drainage.

Between a Reef and a Hard Place: Capacity to Map the Next Coral Reef Catastrophe - Sharyn M. Hickey; Ben Radford; Chris M. Roelfsema; Karen E. Joyce; Shaun K. Wilson; Daniel Marrable; Kathryn Barker; Mathew Wyatt; Harriet N. Davies; Javier X. Leon; John Duncan; Thomas H. Holmes; et al. (Frontiers in Marine Science, 2020)